Les statuts respectifs de citoyen, résident et étranger, à la lumière des chartes des droits. - Brunelle, Christian; Brun, Henri (Les Cahiers de droit, 1988)
This article seeks to verify the commonly formulated assertion to the effect that the citizen, the resident and the foreigner have in Canada substantially the same rights. Doing so, it goes through the constitutional and ordinary law of the land in order that the consequences of each of the three status be identified and assessed. Of course there are differences. The Constitution, for instance, gives to the citizen only the right to enter and stay in Canada. A distinction which goes to the very reason of the existence of citizenship in a sovereign State. The ordinary law, on the other hand, for practical and obvious reasons, reserves certain social rights for residents only. But on the whole the effective state of the law, constitutional, federal and provincial (in Québec), does not contradict the above mentioned statement. The exceptions that exist do not invalidate it.